A CFB ash-based radiation-proof mortar and preparation method thereof
Barium sulfate is generated by the precipitation reaction of barium salt and CFB slag, which solves the problems of poor stability and insufficient radiation shielding capacity in concrete, and achieves efficient radiation shielding and stability improvement, which promotes the construction of CFB slag Large-scale application in materials.
Patent Information
- Application Number
- CN202310398004.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-14
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-04-14
AI Technical Summary
When CFB ash slag is used in concrete, it has poor stability in the later stage due to the effect of solid sulfur, and it has failed to effectively shield radiation, which limits its large-scale application in building materials.
Barium sulfate is produced by precipitation reaction using barium salt with the encapsulated layer of calcium sulfate in the CFB slag, reducing the calcium sulfate content and wrapping the cured active calcium oxygen, modifying the CFB slag, and introducing a composite dispersant to improve dispersion and reduce crushing value , and the barium sulfate generated by the precipitation reaction is used to shield X-rays and gamma rays.
It significantly improves the later stability of the mortar, reduces the expansion rate, realizes effective shielding of X-rays and gamma rays, overcomes the application of CFB slag in building mortar, and has important economic and environmental value.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to a CFB ash-slag-based radiation-proof mortar and a preparation method thereof. Background Art
[0002] CFB ash refers to the solid waste discharged after sulfur-containing coal is mixed with a sulfur-fixing agent in a certain proportion in a circulating fluidized bed boiler for combustion and sulfur fixation. The CFB fly ash discharged from the flue and collected by the dust collector is obtained, and the CFB slag discharged from the bottom of the furnace is collectively called CFB ash. At present, CFB ash has problems such as large emissions and low comprehensive utilization rate, which seriously restricts the development of the circulating fluidized bed coal-fired power generation industry and causes huge pollution to the ecological environment. Therefore, based on the consideration of vigorously absorbing industrial solid waste CFB ash and promoting the sustainable development of the coal-fired power industry, it is necessary to carry out large-scale, high-value-added application research on CFB ash.
[0003] CFB ash has the characteristics of volcanic ash activity, and using CFB ash as raw materials in the building materials industry for resource utilization is an important way to dispose of CFB ash and relieve emission pressure. However, due to the sulfur fixation effect in the production process of CFB slag, there are a large number of sulfur-containing minerals (Ⅱ-CaSO4) and free calcium oxide (f-CaO), of which most of f-CaO is wrapped by Ⅱ-CaSO4. After the Ⅱ-CaSO4 wrapping layer is hydrated, f-CaO begins to hydrate, which easily causes problems such as poor stability of mortar concrete materials in the later stage, restricting its large-scale application in concrete. Summary of the invention
[0004] The main purpose of the present invention is to provide a CFB ash slag-based radiation-proof mortar in view of the problems and shortcomings of the prior art. The mortar uses a barium salt and a calcium sulfate coating layer of f-CaO in the CFB slag to undergo a precipitation reaction to generate barium sulfate, thereby reducing the content of calcium sulfate. The generated barium sulfate coats and solidifies the f-CaO, effectively solving the problems of poor stability of the mortar in the later stage. In addition, the coating layer of barium sulfate generated by the precipitation reaction can well shield X-rays and gamma rays, thereby playing a role in radiation protection in the mortar. The preparation method involved is relatively simple, easy to operate, and suitable for popularization and application.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A CFB ash slag-based radiation-proof mortar, wherein the components and their weight proportions include: 60-70 parts of modified CFB slag, 17-19 parts of cement, 13-15 parts of CFB fly ash, 0.2-0.4 parts of water reducing agent, and 15-18 parts of water; the modified CFB slag is obtained by subjecting the CFB slag to a precipitation reaction using a soluble barium salt solution.
[0007] In the above scheme, the CFB slag passes through a 4.75 mm sieve, wherein the SO3 content is 3 to 18 wt%; the f-CaO content is 2 to 8 wt%; and the loss on ignition is 2 to 4 wt%.
[0008] In the above scheme, the SO3 content in the CFB fly ash is 0-3wt%; the f-CaO content is 0-2wt%; the ignition loss is 1-2wt% and the specific surface area is 320-380m 2 / kg.
[0009] In the above scheme, the cement is one or more of PO 42.5, 42.5R, 52.5, 52.5R, etc., and the relevant performance complies with GB 175-2020.
[0010] In the above scheme, the water reducing agent is a polycarboxylic acid water reducing agent, the water reducing rate is 15-25%, and the solid content is 10-20%.
[0011] In the above scheme, the specific preparation steps of the modified CFB slag include: adding the CFB slag to a soluble barium salt solution containing a composite dispersant, impregnating it under stirring (the stirring speed of the stirrer is 100-300r / min), and then sieving (0.075mm sieve) and drying.
[0012] In the above scheme, the concentration of the barium salt solution is 20-30wt% and the temperature is 60-80℃
[0013] In the above scheme, the dispersant is compounded by polyacrylamide and hydroxymethyl cellulose ether in a mass ratio of 4:6 to 5:5; wherein the molecular weight of polyacrylamide is 8 to 16 million; and the molecular weight of hydroxymethyl cellulose ether is 8,000 to 110,000.
[0014] In the above scheme, the amount of the composite dispersant used is 4-8wt% of the mass of the barium salt solution.
[0015] In the above scheme, the soluble barium salt is one or more of barium chloride, barium nitrate and the like.
[0016] In the above scheme, the immersion treatment time is 1 to 2 hours.
[0017] In the above scheme, the mass ratio of the CFB slag to the soluble barium salt solution is 1:(5-10).
[0018] The preparation method of the CFB ash-based radiation-proof mortar comprises the following steps:
[0019] 1) Weigh the raw materials according to the proportion, and the components and their weight proportions include: 60-70 parts of modified CFB slag, 17-19 parts of cement, 13-15 parts of CFB fly ash, 0.2-0.4 parts of water reducer, and 15-18 parts of water;
[0020] 2) Add the weighed modified CFB slag, cement, and CFB fly ash into a mixer, stir evenly, add water and a water reducing agent, and stir evenly to obtain the CFB ash-based radiation-proof mortar.
[0021] The principle of the present invention is:
[0022] The CFB slag is soaked in a soluble barium salt solution containing a composite dispersant in advance, and the barium salt is used to react with the calcium sulfate coating layer of f-CaO in the CFB slag to generate barium sulfate, thereby reducing the content of calcium sulfate. The generated barium sulfate can well coat and solidify f-CaO, effectively solving the problem of poor stability of the mortar in the later stage. At the same time, the introduced composite dispersant can effectively solve the agglomeration problem caused by the hydration reaction of the active components in the soluble barium salt when treating the CFB slag, and at the same time reduce the crushing value of the modified CFB slag and improve the firmness. In addition, the coating layer of barium sulfate generated by the precipitation reaction can well shield X-rays and gamma rays, thus playing a radiation protection role in the mortar.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1) The CFB ash-based radiation-proof mortar of the present invention has a low expansion rate and good stability, and can well shield X-rays and gamma rays, thus playing a role in radiation protection;
[0025] 2) The present invention overcomes the problems of poor stability in the later stage caused by excessively high content of calcium and sulfur components when CFB slag is used in building mortar by modifying CFB slag, and can largely absorb solid waste CFB ash slag, which has important economic and environmental value;
[0026] 3) The preparation process of the present invention is simple, pollution-free and low-cost. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Example 1
[0029] A CFB ash-based radiation-proof mortar, the preparation method of which comprises the following steps:
[0030] 1) Sieve the CFB slag through a 4.75 mm sieve and take the undersize portion;
[0031] 2) Add the prepared barium chloride solution (30 parts of barium chloride, 70 parts of water; temperature is 65°C) and 5 parts of composite dispersant into a stirring device, add 20 parts of CFB slag under stirring conditions and soak for 1 hour (maintain stirring conditions); obtain modified CFB slag, lay it outdoors and dry it naturally, and obtain modified CFB slag with good dispersibility;
[0032] 3) According to the proportions described in Table 1 (CFB slag modified without step 2) is introduced as a comparative example; the same below), the weighed modified CFB slag, cement, and CFB fly ash are added into a mixer, dry-mixed evenly, water and a water reducing agent are added, and stirred evenly to obtain the CFB ash-based radiation-proof mortar;
[0033] In this embodiment, the CFB slag used is provided by a coal-fired power plant in Shanxi, and its SO3 content is 16.4wt%; f-CaO content is 3.6wt%; and the ignition loss is 2.3wt%; the CFB fly ash is provided by a coal-fired power plant in Shanxi, and its SO3 content is 2.3wt%; f-CaO content is 1.2wt%; and the ignition loss is 1.6wt%, and the specific surface area is 334m 2 / kg; the cement is commercially available P.O42.5 cement; the water reducer is a commercially available polycarboxylic acid water reducer with a water reduction rate of 20%; the dispersant is a mixture of polyacrylamide and hydroxymethyl cellulose ether in a mass ratio of 4:6, wherein the molecular weight of the polyacrylamide is 10 million; the molecular weight of the hydroxymethyl cellulose ether is 95,000, and the dosage is 5wt% of the barium salt solution.
[0034] Table 1 Mixing ratio (kg / m 3 )
[0035] cement CFB fly ash CFB slag water Water reducing agent Example 1 280 220 1000 260 6 Comparative Example 1 280 220 1000 260 6
[0036] Note: The CFB slag used in Comparative Example 1 is the unmodified CFB slag with a particle size of 0-4.74 mm as described in step 1). After demoulding for 24 hours after forming, the two groups of mortars in Comparative Example 1 and Example 1 were both immersed in 20±1°C water for curing to the specified age.
[0037] The mortars obtained in this embodiment and the comparative example were tested for expansion performance and radiation protection performance, and the results showed that the 7d, 28d and 90d expansion rates of the CFB ash-based radiation-proof mortar obtained in this embodiment were 0.12%, 0.36% and 0.38% respectively; the expansion rate changed little from 28d to 90d, indicating that the mortar had good stability in the later stage; the 7d and 28d compressive strengths were 18.96MPa and 40.45MPa. The radiation protection performance met the Type I protection effect in JCT 2676-2022; while the 7d, 28d and 90d expansion rates of the CFB ash mortar obtained in comparative example 1 were 4.8%, 16.9% and 23.5% respectively; the expansion rate changed greatly from 28d to 90d, indicating that the mortar had poor stability in the later stage, and the 7d and 28d compressive strengths were 16.32MPa and 35.13MPa; at the same time, it could not shield X-rays and gamma rays, and had no radiation protection effect.
[0038] Example 2
[0039] A CFB ash-based radiation-proof mortar, the preparation method of which comprises the following steps:
[0040] 1) Sieve the CFB slag through a 4.75 mm sieve and take the undersize portion;
[0041] 2) Add the prepared barium chloride solution (10 parts of barium chloride, 10 parts of barium nitrate, 80 parts of water; the temperature is 70°C) and 7 parts of composite dispersant into a stirring device, add 15 parts of CFB slag under stirring conditions and soak for 1.5 hours (maintain stirring conditions), lay it outdoors and air dry naturally to obtain modified CFB slag with good dispersibility;
[0042] 3) According to the proportions described in Table 2, the weighed modified CFB slag, cement, and CFB fly ash are added into a mixer, dry-mixed evenly, and water and a water reducing agent are added and mixed evenly to obtain the CFB ash-based radiation-proof mortar.
[0043] The CFB slag used was provided by a coal-fired power plant in Shanxi, with a SO3 content of 15.8wt%, f-CaO content of 3.2wt%, and a loss on ignition of 1.8wt%. The CFB fly ash was provided by a coal-fired power plant in Shanxi, with a SO3 content of 1.6wt%, f-CaO content of 1.1wt%, and a loss on ignition of 1.4wt%, and a specific surface area of 326m 2 / kg. The cement is commercially available PO 42.5 cement; the water reducer is commercially available polycarboxylic acid water reducer with a water reduction rate of 18%; the composite dispersant is a mixture of polyacrylamide and hydroxymethyl cellulose ether in a mass ratio of 5:5, wherein the molecular weight of the polyacrylamide is 12 million; the molecular weight of the hydroxymethyl cellulose ether is 100,000, and the dosage is 7wt% of the barium salt solution.
[0044] Table 2 Mixing ratio (kg / m3 )
[0045] cement CFB fly ash CFB slag water Water reducing agent Example 2 271 200 997 270 5.4 Comparative Example 2 271 200 997 270 5.4
[0046] Note: The CFB slag used in the comparative example is untreated CFB slag with a particle size of 0-4.74 mm. After demoulding for 24 hours after forming, the two groups of mortars in comparative example 2 and example 2 were both immersed in 20±1°C water for curing to the specified age.
[0047] After testing, the 7d, 28d and 90d expansion rates of the CFB ash-based radiation-proof mortar obtained in this embodiment are 0.09%, 0.24% and 0.26% respectively; the mortar expansion rate from 28d to 90d changes in a small range, indicating that the mortar has good stability in the later stage; the radiation protection performance meets the Type II protection effect in JCT 2676-2022. The 7d, 28d and 90d expansion rates of the CFB ash-based radiation-proof mortar obtained in Comparative Example 2 are 8.7%, 14.36% and 17.8% respectively; the mortar expansion rate from 28d to 90d changes in a large range, indicating that the mortar has poor stability in the later stage; at the same time, it cannot shield X-rays and gamma rays and has no radiation protection effect.
[0048] Example 3
[0049] A CFB ash-based radiation-proof mortar, the preparation method of which comprises the following steps:
[0050] 1) Sieve the CFB slag through a 4.75 mm sieve and take the undersize portion;
[0051] 2) Add the prepared barium chloride solution (20 parts of barium nitrate, 80 parts of water; temperature is 80°C) and 8 parts of composite dispersant into a stirring device, add 18 parts of CFB slag under stirring conditions and soak for 2 hours; during this process, stir the CFB slag, lay it out and dry it naturally; and obtain modified CFB slag with good dispersibility;
[0052] 3) According to the proportions described in Table 3, the weighed modified CFB slag, cement, and CFB fly ash are added into a mixer, dry-mixed evenly, and water and a water reducing agent are added and mixed evenly to obtain the CFB ash-based radiation-proof mortar.
[0053] The CFB slag used was provided by a coal-fired power plant in Shanxi Province, with a SO3 content of 17.2wt%, f-CaO content of 2.8wt%, ignition loss of 3.2wt%, and crushing value (0.36-4.75mm) of 50.6%. The CFB fly ash was provided by a coal-fired power plant in Shanxi Province, with a SO3 content of 2.8wt%, f-CaO content of 1.8wt%, ignition loss of 1.3wt%, and specific surface area of 354m 2 / kg. The cement is commercially available PO 42.5 cement; the water reducer is commercially available polycarboxylic acid water reducer with a water reduction rate of 23%; the dispersant is a mixture of polyacrylamide and hydroxymethyl cellulose ether in a mass ratio of 4.5:5.5, wherein the molecular weight of polyacrylamide is 13 million; the molecular weight of hydroxymethyl cellulose ether is 88,000, and the dosage is 8wt% of the barium salt solution.
[0054] Table 3 Mixing ratio (kg / m 3 )
[0055] cement CFB fly ash CFB slag water Water reducing agent Example 3 240 260 1100 280 5 Comparative Example 3 240 260 1100 280 5
[0056] Note: The CFB slag used in the comparative example is untreated CFB slag with a particle size of 0-4.74 mm. After demoulding for 24 hours after forming, the two groups of mortars in comparative example 3 and embodiment 3 were both immersed in 20±1°C water for curing to the specified age.
[0057] After testing: the crushing value (0.36-4.75mm) of the modified CFB slag obtained in step 2) of this embodiment is 18.3%, and the dispersibility is good; the 7d, 28d and 90d expansion rates of the CFB ash-based radiation-proof mortar obtained in step 3) are 0.05%, 0.12% and 0.13% respectively; the change range of the mortar expansion rate from 28d to 90d is small, indicating that the mortar has good stability in the later stage; the radiation protection performance meets the Type III protection effect in JCT 2676-2022. The 7d, 28d and 90d expansion rates of the CFB ash mortar in comparative example 2 are 6.5%, 10.3% and 19.6% respectively; the change range of the mortar expansion rate from 28d to 90d is large, indicating that the mortar has poor stability in the later stage; it cannot shield X-rays and gamma rays, and has no radiation protection effect.
[0058] Comparative Example 4
[0059] A CFB slag-based aggregate, which is prepared in substantially the same manner as the modified CFB slag described in Example 3, except that in step 2), no composite dispersant is introduced or only a single polyacrylamide is introduced.
[0060] The results show that when no dispersant is added, the CFB slag exhibits serious agglomeration during the soaking reaction; while when a single polyacrylamide is introduced, the dispersion effect of the modified CFB slag is poor, and the crushing value (0.36-4.75 mm) of the modified CFB slag is 48.6%.
[0061] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.
Claims
1. A CFB ash-based radiation-proof mortar, characterized in that: The components and their weight proportions include: 60-70 parts of modified CFB slag, 17-19 parts of cement, 13-15 parts of CFB fly ash, 0.2-0.4 parts of water reducing agent, and 15-18 parts of water; the modified CFB slag is obtained by precipitating the CFB slag with a soluble barium salt solution; The specific preparation steps of the modified CFB slag include: adding the CFB slag to a soluble barium salt solution containing a composite dispersant, performing an immersion treatment under stirring conditions, and then screening and drying; the dispersant is a composite of polyacrylamide and hydroxymethyl cellulose ether in a mass ratio of 4:6-5:5; the immersion treatment time is 1-2 hours; The CFB slag passes through a 4.75 mm sieve, wherein the SO3 content is 15.8-18 wt%; the f-CaO content is 2-8 wt%; and the ignition loss is 2-4 wt%.
2. The CFB ash-based radiation-proof mortar according to claim 1, characterized in that: The CFB fly ash has a SO3 content of 0-3wt%, a f-CaO content of 0-2wt%, a loss on ignition of 1-2wt%, and a specific surface area of 320-380 m 2 / kg.
3. The CFB ash-based radiation-proof mortar according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is 15-25%.
4. The CFB ash-based radiation-proof mortar according to claim 1, characterized in that: The concentration of the barium salt solution is 20-30wt%, and the temperature is 60-80°C.
5. The CFB ash-based radiation-proof mortar according to claim 1, characterized in that: The molecular weight of the polyacrylamide is 8 to 16 million; the molecular weight of the hydroxymethyl cellulose ether is 8,000 to 110,000.
6. The CFB ash-based radiation-proof mortar according to claim 1, characterized in that: The dosage of the composite dispersant is 4-8 wt% of the mass of the barium salt solution; the mass ratio of the CFB slag to the soluble barium salt solution is 1:(5-10).
7. The method for preparing the CFB ash-based radiation-proof mortar according to any one of claims 1 to 6, characterized in that: The steps include: 1) Weigh the raw materials according to the proportion. The components and their weight proportions include: 60-70 parts of modified CFB slag, 17-19 parts of cement, 13-15 parts of CFB fly ash, 0.2-0.4 parts of water reducer, and 15-18 parts of water; 2) The weighed modified CFB slag, cement and CFB fly ash are mixed evenly, and water and a water reducing agent are added and mixed evenly to obtain the CFB ash-based radiation-proof mortar.
Citation Information
Patent Citations
The Preparation Method of Steel Fiber Reinforced Ultra-high Performance Concrete by Synergistic Utilization of Multi-solid Waste
AU2020101096A4
The preparation method and application of Cementing material containing large amount of waste incineration fly ash and slag
AU2020101816A4
Carbon fiber reinforced cement and preparation method thereof
CN103466979A
Method used for making bricks from domestic waste incineration fly ash and furnace slag
CN108314366A
Anti-radiation concrete and preparation method thereof
CN112010593A